FONTES DE ADUBAÇÃO NITROGENADA E SEUS REFLEXOS NA PRODUTIVIDADE DE TRIGO - Ubessi, Cassiane; Krüger, Cleusa A. M. B.; Pinto, Fernando B.; Battisti, Gabriel K.; Silva, José A. G. d.; Gaviraghi, Juliano (Salão do Conhecimento, 2013)
Resumo